PERSOALAN ORTOGRAFI UNTUK BUNYI HAMBAT-GLOTAL DALAM BAHASA MELAYU LOLOAN BALI - Suparwa, I Nyoman (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 15 (2008): September 2008, 2008)
Abtract Malay language of Loloan Bali as one of the traditional language in Indonesia should get a proper attention in accordance with the mandate of UUD 1945. This language is used by Loloan society which is a combination of some ethnics such as Malay-Pontianak, Bugis-Makassar, Arab, Java, and Bali living in Loloan territory and the shore of Negara-Jembrana, Bali. In it’s development, this language lives contiguous and much influenced by Balinese language as a majority language in Bali and also Indonesian language as a national language in Indonesia. Until nowadays, this language has not used yet as an educational language and it still has not writing system yet (orthography). The limited orthography used in this language is the Indonesian spelling system. The orthography of glotal blocked sound in Malay language of Loloan Bali is still leaving an issue caused by two things. First, the symbol of glotal blocked sound in the traditional languages of Indonesia is still not showing a uniformity. As in Madura language, there is used the symbol of alphabet q, and Malay language of Pontianak use the symbol ?, meanwhile Klon language (traditional language used in Alor island) use the diakritik symbol (‘). Second, the glotal blocked sound in Malay language of Loloan Bali is not fully characterized as alophonic or phonemic system. The untotallity of its characteristic describes the dynamic of Malay languge of Loloan Bali which is formerly characterized as phonemic system and now it shows the unclear of phonemic system charavteristic become alophonic system characteristic (only in the speech variation) as in Indonesian and Balinese language. Academic research called as linguistic about orthography of glotal blocked sound in Malay language of Loloan Bali suggest the use of diakritic symbol (‘), while the symbol ? is used for the phonetic and phonemic writing. The symbol q is not suggested to use because alphabetic symbol is the symbol of unvoiced uvular blocked sound. The diacritic symbol is used for such words and such distribution only. The use of this symbol is proposed to use only in some words which reflects the special characteristics of the phonetic system of Malay Language of Loloan Bali and it could occuring ambiguity in several words if there is no differences between glotal blocked sound and velar blocked sound.